Answer:
![3 {x}^(3) - 25 {x}^(2) + 35x - 23 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/x05hgld64jl5vnerttv2ks839vz6sh1k4x.png)
Explanation:
We want to create an equation that will have the solution
![x = (1)/(3),x = 4 + √(7)i,x = 4 - √(7)i](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j0g8f0obbngzbh6sn0rar4yalmgwgcxh33.png)
This implies that:
![3x -1= 0,x -( 4 + √(7)i) = 0,x - ( 4 - √(7)i) = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hve89jjodhvc6wtxfanol5ch7cueiqm188.png)
We put the roots in factored form by reversing the zero product principle to get:
![(3x -1)(x -( 4 + √(7)i))(x - ( 4 - √(7)i)) = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lo40878fgqs0olhmts3d8vizz85h0n8p4i.png)
We expand the last two parenthesis to get:
![(3x - 1)( {x}^(2) - 4x + √(7)ix - 4x - √(7)ix + 16 - 7 {i}^(2)) = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9yszyfts7xi0pv1n2koshczxal4y2ksphp.png)
We simplify to get:
![(3x - 1)( {x}^(2) - 8x + 23) = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dt7b15o1rbycthsrx8k4d0oya90qgc81l0.png)
We expand further to obtain:
![3 {x}^(3) - 25 {x}^(2) +35x - 23 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r8f4vmvjx7nreilvo8xn9f59bznpk1ov6f.png)